Ahlul Bait Nabi Noble's Characters as Inspiration in Educational Management - Badaruddin, Kemas; Zailia, Siti; Ramadhan, Syahrul; Arafah Pramasto (Sinergi International Journal of Islamic Studies, 2025)
The descendants of the Prophet Muhammad or commonly called the "Ahlul Bait" of the Prophet are a group that is respected in Islamic traditions across schools of thought. There are many legacies of scientific thought and exemplary that can be guided by the Ahlul Bait through a number of central figures, namely Ali bin Abi Talib RA and his descendants. This paper seeks to reveal their noble legacy as an inspiration for the field of leadership in Education Management. The method used is of a qualitative type, namely library research with an analytical emphasis to present descriptive data. This research proves that the nobility of Ahlul Bait Nabi can inspire education managers. The Karbala incident taught a manager the importance of understanding the consequences of the position he holds. Education Management also requires a leader who is able to manage the organization and be careful in choosing individuals who are responsible for a position, these two things can be guided by the text of Ali's letter to the Governor of Egypt he appointed, Malik Al-Asytar. In addition to managerial abilities, a leader must not ignore the virtue of being gentle and fair, such as in giving appreciation and appreciation to the achievements of subordinates, this is exemplified by Ali Zainal Abidin and Musa Al-Kadzhim through the story of the liberation of religious slaves and repentance his sins. Ali RA also emphasized that leaders carry out periodic assessments of their subordinates.